Eksplorasi Etnomatematika pada Benteng Marlborough - Hesti Anggi Astuti; Dafid Setiana; Denik Agustito (UNION : Jurnal Ilmiah Pendidikan Matematika, 2021)
This research aims to explore the mathematic content in school. The methodin this research is a qualitative research mrthod with ethnogrsphic approach. The data collection techniques are carried out by observation, interview, and documentation.The result of the study show that the mathematical content of fort Marlborough are: triangle, trapezoid, rectangle square and beam. While the mathematical concept that can be developed is to looking for surface area, perimeter and volume contained in the geometric shape of the fort Marlborough